Macroporous thermosensitive poly(HEMA-coNIPAAm) hydrogels for controlled drug delivery application - Setiyorini, Yuli (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Controlled delivery systems of a predetermined dose over a sustained period have been used to overcome the shortcomings of conventional dosage forms. This is because the controlled drug delivery system can provide sustained therapeutic level of drug concentration without toxicity and convenience for patients. It would be more beneficial and ideal if the drug could be delivered by a device that would respond to external environmental change. Therefore, the correct amount of drug would be released upon the stimulation of such a temperature change. The purpose of study is synthesis of macroporous thermal responsive poly(HEMA-co-NIPAAM) hydrogels by free radical polymerization for controlled drug delivery applications. Effect of varying water and HEMA-NIPAAm ratio in the monomer mixture were resulted interconnected macroporous structure. From the result, 5HEMA15NIPAAm was showed the most rapid responsiveness in swelling ratio, polymer volume fraction, swelling and deswelling kinetics. The high drug loading capacity was achieved at or below ambient temperature, whilst the release profile was revealed sustain release of conventional anti-inflammatory drug; prednisolone 21 hemisuccinate sodium salt. In general, incorporating appropriate amount of water and HEMA-NIPAAm ratio can improve the swelling properties, drug loading capacity and drug release profile, which can be use for sustained release of various medication.Key words: macroporous, thermosensitive hydrogel, controlled drug delivery application